Understanding and reducing the disaster risk of landslide-induced tsunamis: a short summary of the panel discussion in the World Tsunami Awareness Day Special Event of the Fifth World Landslide Forum - Shinji Sassa; Stephan T. Grilli; David R. Tappin; Kyoji Sassa; Dwikorita Karnawati; Viacheslav K. Gusiakov; Finn Løvholt (Landslides, 2022)
A World Tsunami Awareness Day Special Event was held in hybrid mode on 5 November 2021, during the Fifth World Landslide Forum, in Kyoto, Japan. In this context, a panel discussion was organized across America, Europe, and Asia, with the goal to better understand and reduce the disaster risk of landslide-induced tsunamis, consistent with the Kyoto Landslide Commitment 2020. This article presents a short summary of this panel discussion.